Recovery of balance and walking in people with ataxia after acute cerebral stroke: study protocol for a prospective, monocentric, single-blinded, randomized controlled trial - Meier, Patricia; Mayer-Suess, Lukas; Kiechl, Stefan; Pachmann, Ulrike; Greimann, Raphaela; Kofler, Markus; Brenneis, Christian; Grams, Astrid; Steiger, Ruth; Seebacher, Barbara (Frontiers in Stroke, 2024)
Introduction Posterior circulation stroke can lead to ataxia, manifesting in a loss of coordination and balance. Patients experience difficulty in activities of daily living and an increased risk of falling, both profoundly affecting quality of life. In individuals with neurodegenerative diseases, coordination exercises have been shown to lead to a reduction in ataxic symptoms. There is, however, limited evidence on the effect of physical therapy, specifically coordination exercises in patients with stroke-related ataxia. We therefore present a study protocol for a prospective trial. Methods The purpose of this trial is to investigate the effects of coordination exercises compared to standard physiotherapy on balance and walking in ataxic stroke patients. Therefore, a prospective, single-blinded randomized controlled trial is currently ongoing at the Clinical Department of Neurology, Medical University of Innsbruck, Austria, in collaboration with two local rehabilitation facilities in Austria, Hochzirl Hospital and the Clinic for Rehabilitation Münster. Balance is the primary outcome of the study as assessed using the Berg Balance Scale. Secondary outcomes are concerned with walking, risk and number of falls, independence in daily life, and quality of life, rated using appropriate scales and scores. Patients are allocated applying a 1:1 ratio and a stratified block randomization. In both groups recruited individuals undergo five 45-min treatment sessions per week, totaling 20 sessions of coordination exercises (IG) or standard physiotherapy (CG) over the course of 4 weeks. Data is collected at the baseline (T0), after the 4-week supervised practice (T1), and after another 8 weeks of independent home-based training (T2). Discussion This is the first randomized controlled trial investigating the effects of coordination exercises on balance and walking in people with stroke-related ataxia. As stroke guidelines emphasize the limited evidence of treatment for ataxic symptoms, this study aims to contribute further knowledge regarding tailored interventions for these patients. Clinical Trial Registration German Clinical Trials Registry (drks.de). Identifier: DRKS00020825.